Dealer’s perception on various brands of agrochemical products and their promotional activities in nalgonda district of telangana state - Y. RADHA, VIVEKANANDA REDDY, SEEMA and (The Journal of Research, PJTSAU, 2017)
Indian economy is largely agrarian in nature,Â which is contributing about one fifth of the total GDP.Â The occupation of nearly 58 per cent of the population is agriculture. Since a decade, Indiaâ€™s population isÂ on increasing note therefore, to meet the food grainÂ requirement for the increasing population, there mustÂ be intensive agriculture with judicious use of inputsÂ like fertilizers, pesticides, seeds, irrigation etc. InÂ view of the fact that nearly 30 per cent of the potentialÂ food production is lost in India due to the damageÂ caused by the insect pest, plant pathogens, weeds,Â rodents, birds etc., so the use of pesticides hasÂ become absolutely essential . Hence, theÂ agrochemicals industry in India has a vital role in theÂ economy of the country.